Arabic Learning Skill - Muh Barid Nizaruddin Wajdi (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2015)
There are some factors influencing teaching and learning of foreign language. In teaching Arabic, for example, linguistic factors, such as Phonology, Grammatical rules, Morphology, and Vocabulary. Non linguistic factor also influences teaching and learning Arabic, for example, teaching aids, teaching method, age and environment. Teaching method in Arabic is one of the important factor. This article discusses about the Arabic learning skills, and how influenced Arabic teaching